2011
DOI: 10.1186/1472-6963-11-348
|View full text |Cite
|
Sign up to set email alerts
|

Counting on commitment; the quality of primary care-led diabetes management in a system with minimal incentives

Abstract: BackgroundThe aim of the present study was to assess the performance of three primary care-led initiatives providing structured care to patients with Type 2 diabetes in Ireland, a country with minimal incentives to promote the quality of care.MethodsData, from three primary care initiatives, were available for 3010 adult patients with Type 2 diabetes. Results were benchmarked against the national guidelines for the management of Type 2 diabetes in the community and results from the National Diabetes Audit (NDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…13 In the UK NHS, these aspects of care are all either directly or indirectly incentivized under the QOF and have all been shown to have improved in the UK since the introduction of the QOF in 2004. 28 McHugh et al 14 assessed the performance of three primary care-led initiatives in small geographic areas of ROI, and, although they did not compare the overall quality of diabetes care in ROI, the study highlighted the comparable levels of process measures of performance found in selected areas with a structured system of diabetes care, despite the lack of any financial incentives.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the UK NHS, these aspects of care are all either directly or indirectly incentivized under the QOF and have all been shown to have improved in the UK since the introduction of the QOF in 2004. 28 McHugh et al 14 assessed the performance of three primary care-led initiatives in small geographic areas of ROI, and, although they did not compare the overall quality of diabetes care in ROI, the study highlighted the comparable levels of process measures of performance found in selected areas with a structured system of diabetes care, despite the lack of any financial incentives.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are not eligible must pay to attend the GP. In terms of diabetes care, at present there are a variety of care arrangements in place across the country including traditional hospital-based management, shared care between general practitioners (GPs) and hospitals, primary care-led management 8 9 and unstructured opportunistic care. The most recent survey of diabetes management in general practice highlighted the lack of formal integration between settings 10.…”
Section: Introductionmentioning
confidence: 99%
“…Such care must be exercised with competence and technical specificity of the skin, requiring the nursing consultation to perform comprehensive, effective therapy that promotes the best practice in the area of skin health care. (23,25,26) In fact, nursing consultations allow an interpersonal interaction that stimulates the adoption of care for the metabolic control and treatment of chronic injuries. In this case, the consultations demand high therapeutic acuity and technical specificity, determinants for comfort, confidence, decrease of pain, case resolution and greater clinical adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study of 185 people with diabetes who underwent intensive follow-up and education on the prevention of complications for two years, there was a significant reduction in the incidence of wounds higher healing rates, and fewer surgical interventions. (25) Health recovery can be achieved if there is a service network with professionals engaged, especially with primary care as the gateway to the system with a focus on health promotion and protection. (25) Presence of venous injuries that are of long duration and high rates of relapse, have affected more women and have average time greater than four years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation